Pontos de contaminação em queijeiras artesanais no semi árido do Rio Grande do Norte - Rocha, Manuella de Oliveira Cabral (Universidade Federal Rural do Semi-Árido, 2013)
The study was aimed at assessing the sanitary conditions of food handlers, equipment, utensils and environment of, as well as evaluating water, milk and coalho cheese samples from small production artisanal cheesemaking units in Rio Grande do Norte. Samples were collected throughout two months in five traditional cheesemaking units. A checklist was applied and swab samples of handlers, equipment, utensils were analyzed for Staphylococcusaureus and Enterobacteriaceae counts, and environmental swabs were analyzed for Listeria sp. The sanitary conditions were inadequate in 88% of the evaluated items. All swab samples from handlers, equipment and utensils were contaminated with Enterobacteriaceae. Of the 30 environmental swab samples, in four (13%) the presence of Listeria sp. was detected. As for S. aureus, 100% of the handlers samples were positive and 82% of equipment and utensils samples, too; in 53% of samples, values were above those permitted by law for coalho cheese. It was observed that 80% of water samples were off the standard for total and fecal coliforms. Milk and coalho cheese showed high average scores of 2.22 x105 and 1,857 x105 MLN/mL for total coliform. The average Enterobacteriaceae and Staphylococcusaureus counts were 2.293 x10⁵ and 1.27 x 10⁵CFU/g in the milk samples and 1.29 x 10⁵ and 1.92 x 10⁵ CFU/g in the coalho cheese samples. Coagulase-positive staphylococci were observed in 90% of milk samples and 100% of the coalho cheese samples. The high population of these microorganisms during the production stages of artisanal coalho cheese indicated deficiency in hygiene procedures, characterizing the product as unsatisfactory for hygienic conditions presenting risk to consumer health. The majority of small production artisanal cheesemaking units had poor sanitary conditions. All handlers, equipment and utensils showed high microbiological contamination. The presence of these microorganisms can be directly related to the inadequate sanitary conditions. Thus, monitoring production, guiding producers and analyzing the product regularly, to determine the aggravating contamination points are of extreme importance to assure product quality and public health
Contamination points in artisanalcheesemaking units in the semi-arid of Rio Grande do Norte
Keywords: Publichealth; Food hygiene; Microbiological quality; saúde pública; higiene dos alimentos; qualidade microbiológica; CIENCIAS AGRARIAS::MEDICINA VETERINARIA